2007
DOI: 10.1007/s11145-007-9066-x
|View full text |Cite
|
Sign up to set email alerts
|

Tier 3 specialized writing instruction for students with dyslexia

Abstract: Two instructional experiments used randomized, controlled designs to evaluate the effectiveness of writing instruction for students with carefully diagnosed dyslexia, which is both an oral reading and writing disorder, characterized by impaired word decoding, reading, and spelling. In Study 1 (4th to 6th grade sample and 7th to 9th grade sample), students were randomly assigned to orthographic or morphological spelling treatment but all students were taught strategies for planning, writing, and reviewing/revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 44 publications
3
69
0
2
Order By: Relevance
“…Although this number is larger than that identified by Reed (2008), there is clearly need for more studies particularly across age and ability levels. Second, with respect to research design, there were a number of examples of random assignment of individuals to instructional conditions (Abbott & Berninger, 1999;Berninger et al, 2003;Berninger et al, 2008;Kirk & Gillon, 2009;Lyster, 1998Lyster, , 2002Tyler et al, 2003), though many of the other investigators did manage to randomly assign classes. Given that most studies saw morphological instruction as a part of regular classroom instruction and that the instruction usually took place over several weeks or more, the proportion of studies with random assignment of individuals seems reasonable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this number is larger than that identified by Reed (2008), there is clearly need for more studies particularly across age and ability levels. Second, with respect to research design, there were a number of examples of random assignment of individuals to instructional conditions (Abbott & Berninger, 1999;Berninger et al, 2003;Berninger et al, 2008;Kirk & Gillon, 2009;Lyster, 1998Lyster, , 2002Tyler et al, 2003), though many of the other investigators did manage to randomly assign classes. Given that most studies saw morphological instruction as a part of regular classroom instruction and that the instruction usually took place over several weeks or more, the proportion of studies with random assignment of individuals seems reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…For Berninger et al (2008), effect sizes were calculated from F values. No effect size calculations were conducted for the two studies from Tyler, Lewis, Haskill, and Tolbert (2003) because they reported means and standard deviations of percentage change in scores.…”
Section: Notesmentioning
confidence: 99%
“…Similarly, interventions with morphological instruction also seem to improve reading comprehension for students with learning disabilities (Carlisle 2007;Katz & Carlisle, 2009;Lovett et al 2000) and struggling readers (Carlisle 2007;Katz & Carlisle, 2009;Vadasy et al 2006). Studies have also shown that morphological interventions result in improved spelling achievement for students with reading disabilities (Abbott & Berninger, 1999;Berninger et al 2008;Henry 1987;Henry et al 1989;Lovett & Steinbach, 1997) and for students with low achievement in spelling (Robinson & Hesse, 1981). Furthermore, research has also shown that morphological instruction improves vocabulary outcomes for students with learning disabilities (Katz & Carlisle, 2009;Carlisle 2007;Harris 2007) and for low achievers (Carlisle 2007;Katz & Carlisle, 2009;.…”
Section: Literacy Effects In Englishmentioning
confidence: 98%
“…Morphological instruction has been shown to improve decoding for students with reading disabilities (Abbott & Berninger, 1999;Berninger et al 2008;Edwards 1982;Henry 1987Henry , 1988Henry, Calfee, & Avelar-LaSalle, 1989;Lovett et al 2000;Lovett & Steinbach, 1997) and struggling readers (Carlisle 2007;Katz & Carlisle, 2009;Vadasy, Sanders, & Peyton, 2006). Similarly, interventions with morphological instruction also seem to improve reading comprehension for students with learning disabilities (Carlisle 2007;Katz & Carlisle, 2009;Lovett et al 2000) and struggling readers (Carlisle 2007;Katz & Carlisle, 2009;Vadasy et al 2006).…”
Section: Literacy Effects In Englishmentioning
confidence: 98%
“…Recent studies suggest that phonological awareness is not the only meta-linguistic ability that accounts for reading and spelling skills (e.g., Nagy, Berninger, & Abbott, 2006) which has resulted in growing numbers of studies focusing on the training of morphological awareness (Arnbak & Elbro, 2000;Berninger et al, 2008;Elbro & Arnbak, 1996;Lyster, 2002). In the present paper behavioral and neurophysiological effects of morphological awareness training designed by Kargl and Purgstaller (2009) were investigated in two studies.…”
Section: Introductionmentioning
confidence: 99%